Pengelolaan Sumber Daya Manusia Dalam Meningkatkan Komitmen Kerja Karyawan - Eka Rachmawati; Wahdatul Laili; Ade Rizaldi Hidayatullah; Iriani Ismail (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to identify human resource management in increasing work commitment at the Alvarezi Clothing Store, Kamal, Bangkalan Regency. The method used is descriptive qualitative. We use 2 data. Primary and secondary data. Primary data was obtained through direct observation and interviews. Meanwhile, we got secondary data from a collection of literature. The research results show that good human resource management will increase employee commitment and morale.